SINTESIS DAN KARAKTERISASI ARANG AKTIF DARI CANGKANG KEMIRI SEBAGAI ADSORBEN UNTUK MENURUNKAN KADAR AMONIA (NH3) TOTAL SUSPENDED SOLID (TSS) DAN POTENTIAL HYDROGEN (PH) PADA LIMBAH CAIR INDUSTRI TAHU - Hestina, Hestina; Gultom, Erdiana; Purwandari, Vivi; Sitio, Yohandres (CHEDS: Journal of Chemistry, Education, and Science, 2023)
Research has prepared and characterized activated charcoal from candlenut shells as an adsorbent to reduce ammonia levels, total suspended solids, and hydrogen potential in tofu industrial wastewater. The stages of this research include the Production of activated charcoal from candlenut shells with the combustion process at a temperature of 550 0C for 2 hours in the furnace, achieved sieved using a 100 mesh sieve and then chemically activated by soaking the charcoal in phosphoric acid (H3PO4) 4M solution for 24 hours Furthermore, activated charcoal is characterized based on SNI No. 06-2730-1995 which cover moisture content, ash content, volatile matter content, bound carbon content and iodine absorption and based on this research obtained that moisture content (5,56%), ash content (4,96%), volatile matter content (3,2%), bound carbon content (91,84%),) and iodine absorption (224,94mg/g). Before adding charcoal activated in tofu industrial wastewater,  Ammonia levels were 174 mg/L,  total suspended solids 23 mg/L, and hydrogen potential  5. But after adding charcoal-activated Ammonia levels of 7,85 mg/L,  total suspended solids 165 mg/L, and hydrogen potential  6,5. Based on the data ob, trained activated charcoal from candlenut shells can use as an adsorbent to reduce ammonia levels, total suspended solids, and hydrogen potential in tofu industrial wastewater by environmental regulations.